Variation of alkaloid contents and antimicrobial activities of Papaver rhoeas L. growing in Turkey and northern Cyprus - İlkcan Çoban; Gizem Gülsoy Toplan; Berna Özbek; Çağlayan Unsal Gürer; Günay Sarıyar (Taylor & Francis Group, 2017)
Context: Papaver rhoeas L. (Papaveraceae) corn poppy, widely distributed in Turkey, is used to make a cough syrup for children, as a tea for disturbed sleep, for pain relief and as a sedative in folk medicine. Objective: Samples of P. rhoeas collected from eight different locations in Turkey and three from northern Cyprus were investigated for their alkaloid content and screened for their antimicrobial activities. Materials and methods: From the aerial parts of P. rhoeas samples, alkaloids were isolated by column and preparative thin-layer chromatography. The alkaloids were identified by comparing their spectral data (UV, IR and 1H-NMR) and TLC Rf values with those of authentic samples. The antimicrobial study was carried out by microbroth dilution technique against six strains of bacteria and three strains of fungi. Results: Twelve different alkaloids belonging to proaporphine (mecambrine), aporphine (roemerine), promorphinan (salutaridine), protopine (coulteropine and protopine) and rhoeadine (epiglaucamine, glaucamine, glaudine, isorhoeadine, isorhoeagenine, rhoeadine and rhoeagenine) groups were isolated. The most significant activity was observed with the alkaloid extract of P8 against Staphylococcus aureus with a MIC value of 1.22 μg/mL and against Candida albicans with a MIC value of 2.4 μg/mL. Discussion: The results indicate that P. rhoeas samples (P8 and P9), which contain roemerine as their major alkaloid, were the most active extracts.